Remote learning in pandemic times: reflections on teaching practice (Research, Society and Development, 2021)
This study aims to analyze teachers' perceptions about the practices adopted in distance education during the new coronavirus (COVID-19) pandemic. We carried out qualitative research using an online questionnaire to teachers of different educational levels. With this, we perceive an intensification of the difficulties related mainly to accessing and using technologies for educational purposes. These challenges reveal the weaknesses of Brazilian education in terms of its relationship with digital tools since it was possible to detect the lack of teacher training for using these resources. In conclusion, we understand that the teaching posture is decisive for the achievement of educational objectives. Therefore, we suggest deepening discussions on this issue to subsidize studies that contribute to the development of policies oriented to teaching during the period of isolation by COVID-19.